Development and psychometric validation of the frontline health workers’ occupational risk and characteristics in emergencies index (FORCE-index) – The covid Hospital cohort study - Synne Øien Stensland; Kristina Bondjers; John-Anker Zwart; Leiv Arne Rosseland; Dan Atar; Jan Olav Christensen; Dagfinn Matre; Kristin Alve Glad; Tore Wentzel-Larsen; Hilde Wøien; Grete Dyb (Public Health in Practice)
Objectives: A lack of tools for the systematic identification of frontline health workers' changing occupational risks, characteristics, and needs, poses a major barrier to supporting vital personnel to stay in practice through health emergencies and beyond. The current study reports on the development and psychometric evaluation of the Frontline health workers’ Occupational Risk and Characteristics in Emergencies index (FORCE-index). Study design: The Covid hospital study is a large, multisite, four-wave, open cohort study of frontline health workers responding to the first four waves of the COVID-19 pandemic (2020–2022). Methods: 2496 frontline health workers responded to questionnaires assessing various aspects of their work environment. Using exploratory factor analysis, we estimated the latent structure of the FORCE-index at the first and second waves. This structure was evaluated using confirmatory factor analysis at the third and fourth waves. The internal consistency of the instrument's subscales (e.g., factors) was evaluated using omega reliability, Cronbach's alpha coefficient, and mean inter-item correlation. Results: A nine-factor solution provided best fit to the data. These factors mapped onto the following aspects of the work environment; competency, stress management, familiarity, workload manageability, work performance, infection safety, personal protective equipment, social safety, and social support. Internal consistency for the full FORCE-index and the nine factors was satisfactory. Conclusions: The initial psychometric validation indicates that the FORCE-index is a valid measure which can be used by health authorities, services, and institutions to adequately and systematically assess central aspects of frontline health workers’ work environment that are commonly challenged in health emergencies.